1984
DOI: 10.1103/physrevlett.53.659
|View full text |Cite
|
Sign up to set email alerts
|

Optically Inhibited Collisional Dephasing

Abstract: We have performed a photon-echo experiment on the 555.6-nm intercombination line of atomic Yb vapor which demonstrates that an intense laser field acts to inhibit the dephasing resulting from velocity-changing collisions. This finding implies that the optical Bloch equations, which assume that relaxation is independent of the strength of the driving field, cannot correctly describe the behavior of gas-phase samples in all regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…3 and 4 show the dependence of the normalized pure dephasing rate T Ã 2 ð0Þ=T Ã 2 ðOÞ as a function of the Rabi frequency for different parameters of the PLV. As expected from inequalities (8), deviation of T Ã 2 ðOÞ from T Ã 2 ð0Þ becomes substantial at OXK: But if D > K; contrary to the expectations based on the previously published results [8][9][10][11] the dephasing rate first surprisingly increases (see Fig. 3).…”
Section: Article In Presscontrasting
confidence: 66%
See 1 more Smart Citation
“…3 and 4 show the dependence of the normalized pure dephasing rate T Ã 2 ð0Þ=T Ã 2 ðOÞ as a function of the Rabi frequency for different parameters of the PLV. As expected from inequalities (8), deviation of T Ã 2 ðOÞ from T Ã 2 ð0Þ becomes substantial at OXK: But if D > K; contrary to the expectations based on the previously published results [8][9][10][11] the dephasing rate first surprisingly increases (see Fig. 3).…”
Section: Article In Presscontrasting
confidence: 66%
“…Generally, first experimental observation of dephasing under condition O > t c in optical domain was reported twenty years ago [8] for the system Pr 3þ :LaF 3 : Later the influence of strong optical fields on dephasing process was studied for collision induced broadening in a gas [9] and in a ruby crystal [10]. In all papers strong deviations from the Bloch equations were reported with a qualitative conclusion that T 2 approaches 2T 1 when the optical field increases.…”
Section: Introductionmentioning
confidence: 96%
“…Many NMR techniques have been dwelling on this spinlocking feature [14], starting with the well known double nuclear resonance [15]. Similar locking of electronic dipoles has been observed at optical frequency, both in * electronic mail: jean-louis.legouet@lac.u-psud.fr solids [16,17] and gases [18][19][20].…”
Section: Introductionmentioning
confidence: 93%
“…A similar failure of the SBE was subsequently demonstrated by photon echo experiments on Yb vapor. 24 These experiments stimulated researchers to consider generalizations to the standard optical Bloch equations. [25][26][27][28][29][30][31][32][33][34][35][36] In this paper it will be shown that many of these treatments correspond to a certain limit of the GBE.…”
Section: Introductionmentioning
confidence: 99%